Implementation of a Semantic Wave-Based Simulation Computing Platform for Digital Infrastructure Literacy of High School Students - Eka Fitrajaya Rahman; Erna Piantari; Dwi Fitria Al Husaeni; Renisa Nur Kamelia Putri; Eka Fitrajaya Rahman; Erna Piantari; Dwi Fitria Al Husaeni; Renisa Nur Kamelia Putri (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
The background of this research is based on students' low understanding of the concept of inter-computer collaboration which is abstract and difficult to visualize through conventional learning. This research aims to improve students' digital infrastructure literacy through the implementation of a Semantic Wave-based Distributed Computing learning platform and simulations in the classroom. This research used the Classroom Action Research (CAR). The participants were 30 grade XI students majoring in informatics. Data collection was carried out through learning outcome tests based on cycles, student responses, observation sheets, worksheets, and reflection notes. Quantitative data were analyzed using descriptive statistics and paired sample t-tests, while qualitative data were analyzed thematically based on student activities, teacher facilitation, and cycle reflections. The results showed a consistent increase in learning outcomes, with the average score increasing from 59.13 in Cycle I to 73.63 in Cycle II and 83.97 in Cycle III. The paired sample t-test showed a significance value of 0.000 in the comparison of the pre-test with the post-test of Cycle I, and 0.001 in the comparison of Cycle I with Cycle II (Sig. <0.05). Qualitative observations showed increased student engagement, collaboration, communication, and the ability to connect simulation experiences with conceptual terms. The semantic wave pattern helped students move from concrete experiences to contextual transitions, and finally to denser abstract understanding (Semantic Density). Therefore, the semantic wave-based learning intervention was effective in improving students' digital infrastructure literacy in distributed computing through meaningful, interactive, and reflective learning.